(untitled) (Revista de Medicina Clinica, 2017)
Primary headaches, especially migraine and tensional headache are both, a public health issue in children. Due to their prevalence of 1 to 11% in children and 8 to 23% in adolescents in both genders. Considered the first cause of health care consultation, they are a very important cause of school absenteeism and a decrease in the quality of life of children. The objective of this non-systematic review is the analysis of the pathophysiological bases, classification and red flags that support for the differential diagnosis between primary and secondary headaches; Aside from performing an update on the pharmacological and non-pharmacological treatment of the main school-age primary headaches, migraine and tension headache. Rev Med Clin 2017;1:1-14.